Planning with Always Preferences by Compilation into STRIPS with Action Costs - Ceriani, Luca; Gerevini, Alfonso (Proceedings of the International Symposium on Combinatorial Search, 2015)
We address planning with always preferences in propositional domains, proposing a new compilation schema for translating a STRIPS problem enriched with always preferences (and possibly also soft goals) into a STRIPS problem with action costs. Our method allows many STRIPS planners to effectively address planning with always preferences and soft goals. An experimental analysis indicates that such basic planners are competitive with current planners using techniques specifically developed to handle always preferences.